Glucose–insulin–potassium infusion in sepsis and septic shock: no hard evidence yet - van der Horst, Iwan CC (BioMed Central, 2003)
There is no hard evidence yet for a positive effect of glucose–insulin–potassium infusion in sepsis, septic shock or burn patients. Each individual element of the glucose–insulin–potassium regimen, and eventually euglycaemia, should theoretically be beneficial. At present, evidence exists only for reduced mortality with strict metabolic treatment (i.e. blood glucose levels of 4.4–6.1 mmol/l) in critically ill patients admitted to surgical intensive care units, and for better metabolic regulation (i.e. blood glucose levels of 7.0–10.0 mmol/l) in patients with hyperglycaemia and/or diabetes mellitus, and in patients without signs of heart failure (i.e. Killip class I) during acute myocardial infarction.